Pro-poor payments for environmental services: challenges for the government and administrative agencies in Vietnam - Pham Thu Thuy; Hoang, M.H.; Campbell, Bruce M. (Wiley, 2008)
Governments and administrative agencies are likely to play critical roles in determining the success or failure of payments for environmental services (PES) that are directed at the poor. Using Vietnam as a case study, this article explores the roles, progress and likely impact of the government and the administration in the design and implementation of pro-poor PES. The article focuses on the extent to which it is possible to address the high transaction costs involved and the issue of insecure land tenure, as two major constraints to pro-poor PES. The discussion is based on a literature review, open-ended interviews, and a stakeholder workshop. Although pro-poor PES are welcomed by the government, their implementation is difficult because of overlapping structures and functions, critical gaps in PES policies and a limited understanding of them by decision makers, the private sector and communities. Multi-sectoral approaches and further studies to support policy development and capacity building at the local level are necessary to develop pro-poor PES